Tantangan Dan Keberhasilan Peran Perempuan Dalam Partisipasi Politik Swedia Dan Implikasinya Terhadap Keadilan Gender Secara Global - Aulia Ramadhanty; Neysa Naila; Ardli Johan Kusuma (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Women's political participation is a key factor in achieving an inclusive and equitable democracy. This research aims to investigate the role of women in increasing political participation and democracy in Sweden. Qualitative research is used to understand complex and subjective cases by collecting descriptive and unstructured data. The results show that Sweden has achieved significant progress in women's political participation. The country has consistently championed gender equality and ranks fourth in the 2020 Global Gender Gap Index. The gender equality approach as a cornerstone of its politics has brought significant changes in the role of women in politics and government policy. Sweden also acts as a global change agent in promoting gender equality values. The research also identified that gender gaps still exist in Sweden, influenced by structural barriers, political institutions and political culture. Sweden has used quota mechanisms and women's competency preparation to increase women's representation in parliament. However, there is still work to be done to fully address gender inequality. Sweden is an inspiring country in the fight for gender equality and women's empowerment in politics. Quota efforts, competency preparation, and community support are important steps in increasing women's representation in Swedish politics. Gender concepts and feminist perspectives have becGender equality ome the basis for policies that support women to participate in politics, ensure gender equality, and create a more inclusive and fair political environment for everyone.